Clinical pharmacokinetics and pharmacodynamics of ivosidenib, an oral, targeted inhibitor of mutant IDH1, in patients with advanced solid tumors - Fan, Bin (Invest New Drugs, 2019)
Background Mutant isocitrate dehydrogenase 1 and 2 (IDH1/IDH2) enzymes produce the oncometabolite D-2-hydroxyglutarate (2-HG). Ivosidenib (AG-120) is a targeted mutant IDH1 inhibitor under evaluation in a phase 1 dose escalation and expansion study of IDH1-mutant advanced solid tumors including cholangiocarcinoma, chondrosarcoma, and glioma. We explored the pharmacokinetic (PK) and pharmacodynamic (PD) profiles of ivosidenib in these populations. Methods Ivosidenib was administered orally once (QD) or twice (BID) daily in continuous 28-day cycles; 168 patients received ≥1 dose within the range 100 mg BID to 1200 mg QD. PK and PD were assessed using validated liquid chromatography-tandem mass spectrometry assays. Results Ivosidenib demonstrated good oral exposure after single and multiple doses, was rapidly absorbed, and had a long terminal half-life (mean 40–102 h after single dose). Exposure increased less than dose proportionally. Steady state was reached by day 15, with moderate accumulation across all tumors (1.5- to 1.7-fold for area-under-the-curve at 500 mg QD). None of the intrinsic and extrinsic factors assessed affected ivosidenib exposure, including patient/disease characteristics and concomitant administration of weak CYP3A4 inhibitors/inducers. After multiple doses in patients with cholangiocarcinoma or chondrosarcoma, plasma 2-HG was reduced by up to 98%, to levels seen in healthy subjects. Exposure-response relationships for safety and efficacy outcomes were flat across the doses tested. Conclusions Ivosidenib demonstrated good oral exposure and a long half-life. Robust, persistent plasma 2-HG inhibition was observed in IDH1-mutant cholangiocarcinoma and chondrosarcoma. Ivosidenib 500 mg QD is an appropriate dose irrespective of various intrinsic and extrinsic factors. Trial RegistrationClinicalTrials.gov (NCT02073994). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10637-019-00771-x) contains supplementary material, which is available to authorized users.